Occurrence and contribution of alkyl methoxypyrazines in wine tainted by Harmonia axyridis and Coccinella septempunctata. (19th October 2012) - Botezatu, Andreea I; Kotseridis, Yorgos; Inglis, Debbie; Pickering, Gary J
Abstract: BACKGROUND: Ladybug taint (LBT) is a wine fault caused by the inadvertent incorporation of ladybeetles to the wine during the winemaking process. Harmonia axyridis, also known as the multicolored Asian lady‐beetle (MALB), was the only species considered responsible for causing the taint. A second species, Coccinella septempunctata (7 Spot), has recently also been implicated. The main objectives of this study were to identify and quantify the compounds associated with ladybug taint of white and red wine from these two Coccinellidae species ( Harmonia axyridis and Coccinella septempunctata ), and determine the most odor‐active compounds in LBT‐affected wines. RESULTS: Results show that Coccinellidae can contribute dimethyl, isopropyl, sec butyl and isobutyl methoxypyrazine to wine when they are processed with grapes, and that the methoxypyrazine composition varies between MALB and 7 Spot. Isopropyl methoxypyrazine is the major contributor to LBT in wines produced with these ladybeetle species, although sec butyl and isobutyl methoxypyrazine may contribute in MALB‐ and 7 Spot‐affected wines, respectively. Finally, dimethyl methoxypyrazine is reported for the first time in wines not affected by Coccinellidae; the global significance and prevalence of this compound in wine remains to be determined. CONCLUSION: Both Harmonia axyridis and Coccinella septempunctata can contribute alkyl methoxypyrazines, and particularly isopropyl methoxypyrazine, to wine at concentrations that can have a negative impact on wine quality. These findings will allow grape growers and winemakers to be more aware of the risks posed by 7 Spot beetles, and to take the appropriate preventative and remedial actions. Furthermore, this is the first time dimethyl methoxypyrazine is reported in wine, either as an endogenous or Coccinellidae‐derived odorant. © 2012 Society of Chemical Industry